ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA MICROEMPRESA DE ELABORACIÓN Y COMERCIALIZACIÓN DE MUEBLES DE SALA TIPO LINEAL EN EL CANTÓN LOJA - Paucar Calva, Alexandra Elizabeth (2015)
This project is based on a study for the creation of a business development and marketing for the canton of Loja linear furniture, and thus generate jobs, contributing to the socioeconomic development of the town. To start with the study of this project, it has set a general target named: Prepare a Draft Feasibility Study for the development and marketing of linear room furniture in the canton Loja To meet this primary objective methods, techniques and procedures whereby research, develop and test the veracity of the project were used. The methods used were: Inductive: That used it to based on the particularities found in the project feasibility, generalized conclusions and recommendations, Deductive , which it allowed based on the theoretical concepts related to the completion of a project feasibility apply in developing market research , technical, organizational , economic and financial ; Note : The following techniques are applied allowed to know what is done at present the production process and marketing of linear room furniture Survey: Applied to a representative sample of the population of Loja Canton to determine the needs and preferences of the target market in relation to the processing and marketing of linear room furniture, vital business information. 5 The total survey were 398, the total study population was 71,913 families. For the study and analysis of supply, commercial furniture dealers interviewed in general and in particular sold room furniture linear The analysis in the development of each of the feasibility phase of the project enabled me to reach the following conclusions: 1. The market study determined that the company is feasible to implement it according to the data obtained unmet demand of 28,997. The investment amounts totaling 77.322.79 of which 62.93 % is domestic capital and foreign capital 37.07 %. The financial evaluation indicates that the company will recover the capital in one year, three months and 18 days; that for every dollar invested the company wins $ 0.50 Based on the results, it is recommended to implement the project as it will give significant returns for its investors and generates productive development for its investors and socio-economic development for the canton Loja